Aid for trade and least-developed countries’ relationship with international competitiveness - López Peña, Kendall Ariana (2018)
The World Trade Organization’s (WTO) non-reimbursable cooperation program aims to provide aid for trade to least-developed countries (LDCs). These countries are characterized by having a low Human Development Index (HDI) and major problems in core strategic areas such as infrastructure, procedures, institutions, and supportive trade policies. The program’s objective is to develop trade capacity to enhance LDCs’ international competitiveness. The study aims to establish the relationship between Aid for Trade and its effect on the international competitiveness of the 36 WTO least-developed member countries. To draw this relationship, an international competitiveness index was developed, including variables such as domestic competitiveness, human development, exportation performance, and trade openness. The article concluded that there is a weak relationship between Aid for Trade and its effect on LDCs’ international competitiveness, which could improve if LDCs invest in electricity provisions together with port and airport infrastructure.